TRANSPORT NETWORK USING TECHNOLOGY Synchronous Digital Hierarchy - Munich Heindari Sari Eka (Majalah SIKOMTEK, 2003)
Synchronous Digital Hierarchy (SDH) is pemultiplekan hierarchy based on synchronous transmission that has been defined by CCITT (ITU-T). In the world of telecommunications, pemultiplekan series of signals in the transmission problem in terms of branching and insertion (drop and insert) that is not easy, and limitations to monitor and control the transmission network. SDH has two main advantages: the high flexibility in terms of channel configurations on network nodes and improve network management capabilities for both its payload Traffic and network elements.